Crosslinked electrospun zein-based food packaging coatings containing bioactive chilto fruit extracts - Moreno, María Alejandra (2019)
In this work, zein fibers loaded with phenolic-enriched extracts from pulp, seed and skin of orange chilto were collected on polyhydroxyalkanoate (PHA)films through the electrospinning technique, for their potential use as bioactive internal coatings for food packaging applications. The zein fibers were characterized by scanning electron microscopy (SEM), Fourier transform infrared (FTIR)spectroscopy and thermogravimetric analysis (TGA). The water stability of the zein fibers was improved by crosslinking with glutaraldehyde vapors. The encapsulation efficiency of all bioactive phenolic-enriched extracts was greater than 90%. Encapsulation in the zein fibers improved the thermostability of the extracts. Two food simulants (50% ethanol and 3% acetic acid)were used to evaluate the release of the extracts from the crosslinked zein fibers. It was observed that crosslinking delayed the release of phenolic compounds (rosmarinic acid, caffeic acid and its derivates)in both solvents (80% released after 7 days of contact in 50% ethanol and 23 days in 3% acetic acid)and their antioxidant properties were kept. Therefore, this work demonstrates the potential of the developed zein-based encapsulation structures containing chilto extracts to be applied as antioxidant coatings in food packaging structures to contribute to the preservation of both hydrophilic and lipophilic food products.